THE SYSTEM OF JUSTICE AND POLICING IN MAHARAJA SURAJMAL’S REIGN - Singh, Monica; Kumar, Hridayesh (International Journal of Research -GRANTHAALAYAH, 2025)
This paper examines the administration of justice and law enforcement in the Jat kingdom of Bharatpur during the reign of Maharaja Surajmal ( 1707–1763). Drawing on historical evidence and comparative analysis with neighbouring polities, it explores Surajmal’s judicial institutions, customary law, and policing mechanisms. Sources on Mughal and Rajput governance are used to contextualise Surajmal’s system, which adopted many features of the fading Mughal model while retaining local Jat traditions. The study finds that justice in Surajmal’s state was administered through a hierarchy of village panchayats and district courts under the Maharaja’s final authority, with influences from Islamic and customary law. Policing relied on traditional village watchmen and military patrols rather than a modern police force. In comparison, the Mughal Empire maintained a more formal network of qāzī states similarly combined local customs with imperial norms. A table of estimated population sizes highlights the scale of Surajmal’s Bharatpur relative to Mughal and Maratha domains (Table 1). The analysis incorporates archival population data and normative descriptions of legal practice, presenting a detailed picture suitable for scholarly appraisal.